1967
DOI: 10.2134/agronj1967.00021962005900050032x
|View full text |Cite
|
Sign up to set email alerts
|

Social Cohesion of Steers and Sheep as a Possible Variable in Grazing Studies1

Abstract: During a 4‐year study on the comparative productivity of pastures grazed by cattle and sheep, we also observed the social behavior of these species when kept together. We observed that a strong social relationship between steers and sheep will develop and that time will add to the strength of this relationship. Changes in feeding behavior in response to established social relationships might affect animal performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1984
1984
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Visual observations of animal grazing patterns and behavior indicated that during hot summer days, sheep spent more time resting during the day, whereas cattle grazed intermittently. In mixed-species grazing, where only one animal from each animal species was involved (one cow and one sheep), a very strong social relationship has been shown to develop, and time strengthened this relationship (Bond et al, 1967). However, when more than one animal from each species was used, as in our experiment, animals tended to stay within their own species group (Bond et al, 1967).…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Visual observations of animal grazing patterns and behavior indicated that during hot summer days, sheep spent more time resting during the day, whereas cattle grazed intermittently. In mixed-species grazing, where only one animal from each animal species was involved (one cow and one sheep), a very strong social relationship has been shown to develop, and time strengthened this relationship (Bond et al, 1967). However, when more than one animal from each species was used, as in our experiment, animals tended to stay within their own species group (Bond et al, 1967).…”
Section: Discussionmentioning
confidence: 58%
“…In mixed-species grazing, where only one animal from each animal species was involved (one cow and one sheep), a very strong social relationship has been shown to develop, and time strengthened this relationship (Bond et al, 1967). However, when more than one animal from each species was used, as in our experiment, animals tended to stay within their own species group (Bond et al, 1967). In our experiment, in mixed-species pastures, cattle and sheep were separated, often a t opposite ends of the pasture.…”
Section: Discussionmentioning
confidence: 99%
“…Since at least 1962, it has been known that, under certain conditions, a social relationship could be formed between different species (Scott, 1962). Bond et al (1967) reported that cohesiveness appeared to develop between sheep and cattle as a result of their being stocked together on small paddocks. An initial study by Anderson et al (1987) established proof-of-concept that close confinement of sheep and cattle can create cohesiveness (termed a 'bond') between large and small ruminants, with the term 'flerd' (flock+herd) being used to denote the inter-specific association of small ruminant groups remaining with cattle under free-ranging conditions (Anderson et al, 1988).…”
Section: Introductionmentioning
confidence: 99%